Ionic-liquid-facilitated transdermal absorption of lidocaine hydrochloride - Xiaoting Ma; Yangzhe Zhou; Ke Jiang; Yuqi Wen (PLoS ONE, 2026)
The increasing worldwide need for analgesics, along with patients’ aversion to injectable anesthetics and limited compliance, highlights the necessity for noninvasive local anesthesia. However, the skin barrier poses a significant obstacle to the efficient transdermal administration of anesthetics. In this study, we synthesized a new ionic liquid (IL), tetradecylphosphonium hexanoate, by mixing sodium hexanoate and CYPHOS 101 at equimolar ratios. We systematically evaluated the capacity of this IL to improve the transdermal transfer of lidocaine hydrochloride through in vitro skin permeation tests and cytotoxicity investigations in HaCaT cells. The IL significantly enhanced the percutaneous absorption of lidocaine in a concentration-dependent manner. At 80 mM, the permeation efficiency increased by approximately 1.5 times compared with the control group, resulting in a significantly reduced onset time for topical anesthesia. While IL showed minimal cytotoxicity at low concentrations, higher concentrations were linked to increased cytotoxicity. ILs can effectively enhance the permeation of transdermal lidocaine. The ease of synthesizing ILs, their adjustable properties, and good compatibility make them promising for creating advanced topical anesthetics and broadening transdermal drug delivery applications.